The Role of Intercultural Communication in the Adaptation of Minangkabau Migrants to a New Social System in Bekasi City - Irfan Syahfran; Hamluddin Hamluddin; Selvi Musyarofah; Putri Haryati; Muhamad Rifki Fauzan; Elida Zulfa (Fakultas Komunikasi, Sastra, dan Bahasa, 2026)
This study examines the social adaptation process of the Minangkabau community that migrated and settled in Margahayu District, Bekasi City. Using a descriptive qualitative case study approach, it explores the community’s adaptive strategies in a multicultural social environment. Data were collected through semi-structured interviews and participant observation, allowing for detailed accounts of personal experiences and perceptions. Findings reveal that adaptation occurs gradually through social interaction, negotiation of local norms, and intercultural communication. Challenges such as negative stereotypes—particularly the perception of